การศึกษาความหนาที่เหมาะสมของวัสดุเคลือบส่วนต่อประสานต่าง ๆ บนขั้วสังกะสีแอโนดสำหรับแบตเตอรี่สังกะสี-ไอออนแบบประจุกลับได้ - วิชุดา ศิลปสม (จุฬาลงกรณ์มหาวิทยาลัย, 2021)
Zinc ion batteries are one of the most popular alternatives batteries because they are cheap and high safety. However, they still show a unsatisfied cycling performance due to the dendrite formation on the zinc anode. And with repeated use, dendrites have potential to grow resulting in a short-circuit and batteries cell damage. Therefore, this research aims to study and develop zinc electrodes by coating with three carbon including activated carbon (AC), acetylene black (AB), and carbon black (CB). The ratio between carbon and poly vinylidine fluoride (PVDF) binder is 9:1. In addition, CaCO3 was also investigated as the additional additive for the coating. The ratio between the carbon, CaCO3 and the PVDF is 7:2:1. The galvanostatic charge-discharge of a full-cell battery. It showed that the Zn anode battery with the addition of AC or CaCO3 gave better performance than a bare Zn foil anode. They had initial capacities are 163.0 and 138.0 mAh g-1 at 1 A g-1 for AC and CaCO3 while dropping to 41.4 and 46.0 mAh g-1 respectively when compared with 8.7 mAh g-1 of bare Zinc foil anode. After 1000 cycles when these two additives were mixed, the batteries had the initial capacity of the battery is 149.6 mAh g-1 and decreased to 45.2 mAh g-1 after 1000 cycles. When considering together with the electrochemistry analysis, Zn anode coated with pure AC gave the best test results.